Linearization method in reliability problem - Pho, Nguyen Van; Thach, Le Ngoc (Vietnam Journal of Mechanics, 1993)
A method for calculation of reliability of mechanical system by linearization of conditional functions of joint probability around its expectation is considered. A numerical example is given.